Quisiera que me explicara el subjuntivo. Attitudes and perceptions of Spanish Heritage Speakers in Study Abroad Context - Cabal Jiménez, Munia (2019)
This study analizes the perceptions of heritage speakers of Spanish regarding their own language variety and their attitudes and perceptions about studying abroad in Spanish-speaking countries. The perceptions of heritage speakers that participate in a program in Spain for three months, versus heritage speakers that participate in a program in Costa Rica for one month, are analyzed and compared. The goal of this study is to determine if after having participated in study abroad programs focused on Spanish language in these countries, the experience impacts and modifies the perception and understanding on their own heritage speaker variety. If different, the study try to determine in which parameter. The students that participated in the survey are all heritage speakers of Spanish from the USA´s Midwest region (particularly from Illinois), born in the US and mostly of Mexican descent. Data were gathered via  survey applied virtually via Qualtrics or personally, with twenty-four questions about the background of the students before going abroad, perceptions and reactions while taking written and oral placement tests, and their own perception after the program. The questions are focused on the academic experiences in each country of immersion. Key Words: study abroad, heritage speakers, Spanish, attitudes, perceptions.